Pluronic lecithin organogel - Belgamwar, Veena S; Pandey, Mohit S; Chauk, Dhiraj S; Surana, Sanjay J (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this review is to give detail insight of pluronic lecithin organogels (PLOs) as a topical and transdermal drug delivery system. Pluronic lecithin organogel is a microemulsion-based gel that has been effectively used by physicians and pharmacists to deliver hydrophilic and lipophilic drugs topically and transdermally across the stratum corneum. It is thermodynamically stable, viscoelastic, and biocompatible gel composed of phospholipids (lecithin), organic solvent, and polar solvent. Various types of therapeutic agents have been easily incorporated in PLO to improve their topical drug delivery. Pluronic lecithin organogel improves the topical administration of drug mainly because of desired drug partitioning, biphasic drug solubility, and the modification of skin barrier system by organogel components. Beside this, it shows low skin irritation, increases patient compliance, reduces side effects, avoids first pass metabolism, and increases efficiency of drug. In addition, PLO has been shown in vivo and in vitro to modulate the release and permeation of drugs applied transdermally. Thus, in future, it has wide range of applications and opportunities to experiment with various drugs in this type of drug delivery system.